QUALITY OF E-BOOK MATERIAL FOR JAVANESE LANGUGAE FOR ELEMENTARY SCHOOL LEVEL - Subarkah, Taufik; Maruti, Endang Sri (Universitas Muhammadiyah Mataram, 2025)
Abstrak: Penelitian ini bertujuan untuk mengetahui kualitas media pembelajaran berupa e-book berisi materi unggah-ungguh bahasa Jawa untuk siswa sekolah dasar yang telah dikembangkan. Penelitian ini berjenis R&D. Hasil penelitian menunjukkan bahwa kepraktisan produk di kelas rendah memperoleh skor 78,15%, perolehan nilai pada kepraktisan produk di kelas menengah memperoleh skor 90,70%, perolehan nilai pada kepraktisan produk di kelas tinggi memperoleh skor 85,00%, hasil perolehan validasi nilai dari keseluruhan nilai mencapai angka 84,61% sehingga kategori produk dinyatakan cukup praktis untuk digunakan. Hal itu menunjukkan bahwa e-book unggah-ungguh basa Jawa untuk siswa sekolah dasar yang telah dikembangkan berkategori sangat layak dan cukup praktisAbstract: This study aims to determine the quality of learning media in the form of e-books containing Javanese language etiquette material for elementary school students that have been developed. This research is an R&D. The results of the study showed that the practicality of the product in the lower class obtained a score of 78.15%, the value obtained on the practicality of the product in the middle class obtained a score of 90.70%, the value obtained on the practicality of the product in the high class obtained a score of 85.00%, the results of the validation of the value of the overall value reached 84.61% so that the product category was declared quite practical to use . This shows that the Javanese language etiquette e-book for elementary school students that has been developed is categorized as very feasible and quite practical.